The Utilization of Generative AI in Instructional Content Development: A Literature Review - Nurul Asmaya Fitria Hasanah; Baiq Anisya Nelahi Purnadya; Baiq Oriza Januarlinda; Gunawan Gunawan; Nina Nisrina (Indonesian Journal of Applied Science and Technology, 2023)
Generative AI has significant potential to assist educators in developing learning content more quickly, creatively, and adaptively. This study aims to analyze various research on the use of generative AI in educational content development. The method employed was a narrative literature review, with articles retrieved using the Publish or Perish application from the Crossref, Google Scholar, and OpenAlex databases, covering publications from 2014 to 2023. Based on the literature selection process, 19 relevant research articles were identified for analysis. The review findings indicate that generative AI can support teachers and lecturers in developing instructional media, preparing teaching materials, creating assessments, and producing digital learning content more efficiently. However, challenges remain, including limited technological literacy, unequal access to devices, and ethical concerns regarding AI use. In conclusion, this study highlights that the effective use of generative AI in educational content development should be accompanied by the enhancement of educators’ digital competencies and a strong understanding of the ethical aspects of technology use.